2015
DOI: 10.1007/s10072-015-2160-y
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of protection by the selective A2A receptor antagonist SCH58261 after transient focal cerebral ischemia

Abstract: Evidence indicates that the adenosine A2A receptor subtype is of critical importance in stroke. In previous studies, in the model of permanent middle cerebral artery occlusion (pMCAo), the adenosine A2A receptor antagonist, SCH58261, administered soon after ischemia, proved protective against excessive glutamate outflow in the first 4 h after ischemia and against neurological deficit and tissue damage evaluated 24 h after pMCAo. In the present work, we investigated if neuroprotective effect of SCH58261 was mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…However, it is also known that later, hours and days after insult, there is a massive infiltration of blood cells and neuroinflammation that may be inhibited by activation of A 2A receptors located on blood cells. Accordingly, the chronic administration of an A 2A receptor antagonist for 7 days after transient focal ischaemia failed to protect the brain (Melani et al , ), suggesting that A 2A receptor antagonists should be administered for a limited time window of about 4 h after stroke (Pedata et al , ). However, it is important to mention that chronic enhanced levels of adenosine may lead to seizures, through A 2A receptor activation and neurotrophins, suggesting that in this context A 2A receptor antagonists could be useful clinically (Sandau et al ., ).…”
Section: Pathological Role Of Adenosine In Cerebral Ischaemiamentioning
confidence: 99%
“…However, it is also known that later, hours and days after insult, there is a massive infiltration of blood cells and neuroinflammation that may be inhibited by activation of A 2A receptors located on blood cells. Accordingly, the chronic administration of an A 2A receptor antagonist for 7 days after transient focal ischaemia failed to protect the brain (Melani et al , ), suggesting that A 2A receptor antagonists should be administered for a limited time window of about 4 h after stroke (Pedata et al , ). However, it is important to mention that chronic enhanced levels of adenosine may lead to seizures, through A 2A receptor activation and neurotrophins, suggesting that in this context A 2A receptor antagonists could be useful clinically (Sandau et al ., ).…”
Section: Pathological Role Of Adenosine In Cerebral Ischaemiamentioning
confidence: 99%
“…Thus, adenosine receptors could be potential targets for neuroprotection and experimental data support this hypothesis. In particular, it has been demonstrated that CGS21680 agonist for the adenosine receptor A 2A protects brain tissue in a rat model of transient medial cerebral artery occlusion 3 by preventing leucocytes infiltration and neuroinflammation following brain ischemia 4 . Even though experimental studies have demonstrated that modulation of adenosine system could be a viable neuroprotective strategy for ischemic stroke, translation to humans has been hampered by the difficulties in producing molecules that selectively activate A 2A receptors without inducing desensitization and downregulation and by the occurrence of adverse effects at dosages compatible with a therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…As the transient release of glutamate from synapses during ischemia and the early period of reperfusion has been shown to trigger the cascade of neuronal cell death, many studies have focused on identifying therapeutic tools to effectively reduce the excitotoxicity of glutamate. For example, selective blockade of the NMDA receptor or the adenosine receptor attenuated ischemic insults [ 4 5 ]. In addition, accumulating evidence indicates that modulation of the activity of the glial glutamate transporter (GLT-1) provides neuroprotection against brain ischemic insults and even pilocarpine-induced status epilepticus and Alzheimer's disease [ 6 7 8 ].…”
Section: Introductionmentioning
confidence: 99%